2021
DOI: 10.1109/access.2021.3049575
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Limited & Weighted Model Reduction Algorithm With Error Bound: Application to Discrete-Time Doubly Fed Induction Generator Based Wind Turbines for Power System

Abstract: The state-space representations grant a convenient, compact, and elegant way to examine the physical systems, e.g., induction and synchronous generator-based wind turbines, with facts readily available for stability, controllability, and observability analysis. In this paper, the model order reduction of a stable doubly fed induction generator based variable-speed wind turbines model is performed with the aid of the proposed stability preserving balanced realization algorithm based on discrete frequency weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…As a consequence, ROMs obtained are stable, and these techniques yield error bound formula [42]. Remark 8: Similarly, ROMs for decomposed systems (19) and (20) are obtained in similar way as in (49)(50) and (51-52) respectively. Moreover, ROMs obtained are stable and also yield error bound formula [42].…”
Section: B Existing 2-d Stability Preserving Frequency Weighted Mor Techniquementioning
confidence: 74%
See 1 more Smart Citation
“…As a consequence, ROMs obtained are stable, and these techniques yield error bound formula [42]. Remark 8: Similarly, ROMs for decomposed systems (19) and (20) are obtained in similar way as in (49)(50) and (51-52) respectively. Moreover, ROMs obtained are stable and also yield error bound formula [42].…”
Section: B Existing 2-d Stability Preserving Frequency Weighted Mor Techniquementioning
confidence: 74%
“…The frequency limited intervals for 1-D and 2-D systems are given in [48]. Similarly, frequency weighted and limited MOR approaches for power systems are given in [49]- [51].…”
Section: B Literature Reviewmentioning
confidence: 99%
“…The authors showed that SFSS is fast and robust, with a higher classification accuracy, compression ratio, and extremely low computational time. In the work of Bashir et al [34], a model order reduction of a stable doubly fed induction generator based variablespeed wind turbine model was performed with the aid of the proposed stability-preserving balanced realization algorithm based on discrete frequency weights and a limited frequency interval. In contrast to conventional reduction methods, the proposed method produces steady and precise outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the above article [1], two relevant references [2], [3] were missing. The last sentence of Section I-C. should read ''Proposed technique deals with frequency weighted and limited Gramians based MOR approach for the discrete-time systems.…”
mentioning
confidence: 99%
“…The frequency weighted version of proposed work appears in [2] while frequency limited work appears in [3] for continuous time systems. Compared to [2], [3], mathematical model and simulations in [1] are done for frequency weighted and limited scenarios for discrete time systems. ''…”
mentioning
confidence: 99%